Perlindungan Hukum Dalam Konsep Negara Kepulauan (Archipelago State) Terhadap Batas-Batas Wilayah Secara Hukum Internasional - Seri Mughni Sulubara; Murthada Murthada; Amrizal Amrizal; Mira Ariya Putri; Rubiah Rubiah; Yulpa Yanti; Muttmainnah Mahbengi; Novia Mawarni; Andika Saputra; Azahari Zairie Ahmad (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
The concept of Indonesia as an archipelago state was recognized by the world after the United Nations Convention on the Law of the Sea (UNCLOS) was ratified on December 10, 1982, and Indonesia has ratified it with Law Number 17 of 1985. The recognition of Indonesia as an archipelagic state is a great gift for the Indonesian people because jurisdictional waters cover 2/3 of the entire area of the country. The water area becomes one unit with the land. Indonesia is an archipelago that stretches from Sabang to Merauke. The theory used in this research is the theory of legal protection. The theory of legal protection is very relevant to the research made here, because there needs to be legal protection regarding territorial boundaries for Indonesia as an archipelagic state. The research method used regarding the protection of international law in the concept of an archipelago state against international legal boundaries is carried out by means of qualitative descriptive research. The data collection technique or instrument used is library research by studying various books as literature, official documents, laws and regulations, results of previous research, and other literature sources related to the problems studied. Indonesia is a country with the largest number of islands in the world. The 1945 Constitution stipulates that Indonesia is an archipelagic country, namely a country that has many islands, namely 17,480 islands with a coastline length of 95,181 km. The Unitary Republic of Indonesia is an archipelago with the largest number of islands in the world and has abundant wealth, including those contained in its outer islands.